Formulation and Evaluation of Bioactive Composite Hydrogel Nanochitosan from Siwalan Fruit Peel (Borassus flabellifer) against Enterococcus faecalis - Siswanto, Darmawan Chandra; Ramadani, Arfania Laily Rizky; Saputra, Bachren Azra; Putri, Fadia Amalina; Maharani, Marshanda Keysa Putri (Brawijaya University, 2024)
Caries is a bacterial infection of the hard tooth tissue, among the top six diseases in Indonesia. A common pulp capping failure often results from microleakage and contamination by Enterococcus faecalis bacteria. Siwalan (Borassus flabellifer) shell, containing chitosan, has antibacterial properties and supports tissue regeneration. This research aims to create a bioactive composite hydrogel with nano chitosan extract from siwalan shell at concentrations of 0.5%, 1%, and 1.5%, and evaluate its quality and antibacterial effectiveness against Enterococcus faecalis. The study used an experimental post-test only group design with three treatment groups (0.5%, 1%, and 1.5% siwalan shell nano chitosan extract) and two control groups. The nano chitosan extract was prepared through deproteination, demineralization, and deacetylation, followed by formulation and quality testing of the hydrogel. The antibacterial test was conducted using the tube dilution method, and data were analyzed with One-way ANOVA and Tukey HSD tests. The hydrogel's Minimum Bactericidal Concentration (MBC) was found to be 0.5%. The results of statistical tests show that the calculated F value (37.185) is greater than the F table (2.8661) with a sig value of 0.000 (0.000 < 0.05). Thus, the bioactive composite hydrogel nano chitosan extract from siwalan shell effectively inhibits the growth of Enterococcus faecalis and meets the quality parameters for pulp capping material.